Les retombées du pacifisme dans l’œuvre narrative de Jean Giono - Giorgetto Giorgi (Revue Italienne d'Etudes Françaises)
Jean Giono practiced pacifist ideology throughout his life and paid hard for it with two incarcerations in 1939 and 1944. His pacifism, however, takes on two distinctly different aspects in his narrative work. From the 1920s until the start of the Second World War, he celebrated, to a certain utopian extent, the peaceful life, uninvaded by technology, industrialization and profit that the farmers and artisans of Haute-Provence led at the beginning of the 20th century, in an almost timeless atmosphere. In the second part of the century, on the contrary, our author, strongly marked by the events of the Thirties and Forties, changed course and, without renouncing his pacifism, decided to face history. He then describes, especially in the « Cycle du Hussard », the amoral pragmatism of political circles, which ends up inducing the protagonist of the « Cycle » to opt for a kind of anarchism.